A critical, decolonial glance at language teacher education in Brazil: on being prepared to teach - Mastrella-de-Andrade, Mariana; Pessoa, Rosane Rocha (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
The decolonial accounts made by a student teacher motivated us to problematize discourses about the “unpreparedness to teach languages at schools”, recurrent in the area of language teacher education in Brazil, and confront them with accounts of other student teachers and of applied linguistics, poststructuralist and decolonial scholars. In this interpretive study, discussions on the themes language, the subject and teaching, coming from the empirical material, led us to a perspective of teacher education as an “impossible but necessary project” (LOPES; BORGES, 2015) and to the need to educate language teachers “to talk” (SKLIAR, 2006), in view of the great complexity of teaching contexts.